RESEARCH AND DEVELOPMENT OF INSPECTION AND MAINTENANCE METHODS FOR WIND TURBINE GEARBOX - FAN ZhiFeng; SU XuJun; ZHANG Rong; LI FangHuan (Jixie qiangdu)
Wind Turbine Gearbox is an important part of the wind turbine,in the long-term operation will inevitably occur various types of faults,its inspection and maintenance methods will become the focus of scholars. By analyzing the research status of condition monitoring methods and means,fault feature extraction methods and maintenance strategies for wind turbine gearbox,the main problems in the research of inspection and maintenance methods are summarized. Some suggestions are put forward,such as the research of on-line monitoring method and means of wind turbine gearbox based on multi-sensor,the research of intelligent fault diagnosis method of wind turbine gearbox based on multi-source information fusion,the research of preventive maintenance strategy of wind turbine gearbox based on life distribution and real-time monitoring data,etc. It can be used for reference for the research of wind turbine gearbox inspection and maintenance method.